Web based aphasia test using service oriented architecture (SOA) - Voos, J A; Vigliecca, N S; Gonzalez, E A (Journal of physics. Conference series, 2007)
Based on an aphasia test for Spanish speakers which analyze the patient's basic resources of verbal communication, a web-enabled software was developed to automate its execution. A clinical database was designed as a complement, in order to evaluate the antecedents (risk factors, pharmacological and medical backgrounds, neurological or psychiatric symptoms, brain injury -anatomical and physiological characteristics, etc) which are necessary to carry out a multi-factor statistical analysis in different samples of patients. The automated test was developed following service oriented architecture and implemented in a web site which contains a tests suite, which would allow both integrating the aphasia test with other neuropsychological instruments and increasing the available site information for scientific research. The test design, the database and the study of its psychometric properties (validity, reliability and objectivity) were made in conjunction with neuropsychological researchers, who participate actively in the software design, based on the patients or other subjects of investigation feedback.